2021
DOI: 10.5194/esd-2021-4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trivial improvements of predictive skill due to direct reconstruction of global carbon cycle

Abstract: Abstract. State-of-the-art carbon cycle prediction systems are initialized from reconstruction simulations in which state variables of the climate system are assimilated. While currently only the physical state variables are assimilated, biogeochemical state variables adjust to the state acquired through this assimilation indirectly instead of being assimilated themselves. In the absence of comprehensive biogeochemical reanalysis products, such approach is pragmatic. Here we evaluate a potential advantage of h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
(42 reference statements)
2
7
0
Order By: Relevance
“…Nevertheless, our results add confidence to the current practice of indirect reconstruction in carbon cycle prediction systems (Ilyina et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, our results add confidence to the current practice of indirect reconstruction in carbon cycle prediction systems (Ilyina et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Predicting variations in weather and climate yields numerous benefits for economic, social, and environmental decisionmaking (Merryfield et al, 2020). Carbon cycle prediction systems have the ability to predict the near-term evolution of CO 2 fluxes (Li et al, 2019;Lovenduski et al, 2019a, b) and atmospheric CO 2 (Spring and Ilyina, 2020;Ilyina et al, 2021) to constrain the large internal variability of the global carbon cycle (Spring et al, 2020). Predictions require a forecasting model and initial conditions representing observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chosen variables for assimilation and the respective relaxation time are according to previous investigations of decadal climate prediction based on MPI-ESM (Marotzke et al, 2016). Direct assimilation of the carbon cycle related variables is not included because of the limited available data; instead, we found that the global carbon cycle is well represented from the assimilation of physical variables only (Li et al, 2016(Li et al, , 2019Lovenduski et al, 2019b, a;Ilyina et al, 2021), and furthermore, a recent study based on a perfect-model framework (i.e., based on simulations in which the model tries to predict itself) revealed that direct assimilation of the global carbon cycle only brings trivial improvement of predictive skill of the global carbon cycle (Spring et al, 2021).…”
Section: Assimilation Methodsmentioning
confidence: 67%
“…By assimilating observational products of physical variables, the decadal prediction systems are able to reproduce the variations in CO 2 fluxes as found in observation-based products. Decadal prediction systems can then use states from an assimilation simulation as initial conditions for further multi-year predictions of the global carbon cycle (Li et al, 2016(Li et al, , 2019Lovenduski et al, 2019a, b;Ilyina et al, 2021). However, as of now, the state-of-the-art decadal prediction systems are typically forced with a prescribed atmospheric CO 2 concentration without an interactive carbon cycle, i.e., the effect of the changes in CO 2 fluxes are not reflected in the atmospheric CO 2 variations.…”
Section: Introductionmentioning
confidence: 99%